Vaccine-induced SARS-CoV-2 antibody response: the comparability of S1-specific binding assays depends on epitope and isotype discrimination - Schest, Silvia; Langer, Claus; Stiegler, Yuriko; Karnuth, Bianca; Arends, Jan; Stiegler, Hugo; Masetto, Thomas; Peter, Christoph; Grimmler, Matthias (Frontiers in Immunology, 2023)
Background: Quantification of the SARS-CoV-2-specific immune response by serological immunoassays is critical to the management of the COVID-19 pandemic. In particular, neutralizing antibody titers to the viral spike (S) protein have been proposed as a correlate of protection (CoP). The WHO established the First International Standard (WHO IS) for anti-SARS-CoV-2 immunoglobulin (Ig) (NIBSC 20/136) to harmonize binding assays with the same antigen specificity by assigning the same unitage in Binding Antibody Units (BAU)/ml. Method: In this study, we analyzed the S1-specific antibody response in a cohort of healthcare workers in Germany (n = 76) during a three-dose vaccination course over 8.5 months. Subjects received either heterologous or homologous prime-boost vaccination with ChAdOx1 nCoV-19 (AstraZeneca) and BNT162b2 (Pfizer-BioNTech) or three doses of BNT162b2. Antibodies were quantified using three anti-S1 binding assays (ELISA, ECLIA, PETIA) harmonized to the WHO IS. Serum neutralizing antibody levels were determined by surrogate virus neutralization test (sVNT). Binding assays were compared using Spearman’s rank correlation and Passing-Bablok regression. Findings: All assays showed good correlation and similar antibody kinetics correlating with neutralizing potential. However, the assays show large proportional differences in BAU/ml. ECLIA and PETIA, which detect total antibodies against the receptor binding domain (RBD within the S1 subunit, interact similarly with the convalescent plasma-derived WHO IS but differently with vaccine serum, indicating a high sensitivity to the IgG/IgM/IgA ratio. Conclusion: All three binding assays allow monitoring of the antibody response in COVID-19 vaccinated individuals. However, the assay specific differences hinder the definition of a common protective threshold in BAU/ml. Our results highlight the need for thoughtful use of conversion factors and consideration of method-specific differences. To improve the management of future pandemics and to harmonize total antibody assays, we should strive for reference material with well-characterized Ig isotype composition.